Tumour budding – an additional prognostic facto r in colorectal cancer survival - Gülçİn Harman Kamall; Cemal Ulusoy; Nikolovski, Andrej; Sedat Kamall (Termedia, 2023)
Tumour budding (TB) in cancer is a phenomenon of tumour cells forming clusters, and it is associated with an epithelial-mesenchymal transition into the extracellular matrix of the tumour. It has been shown that the presence of TB in colorectal cancer (CRC) is associated with worse overall survival, higher possibility for vessel invasion, lymph node involvement, and distant metastases appearance. In this retrospective study TB presence in operated patients for CRC is analysed. In the data from 81 patients, 26 presented with TB. Analysis revealed high statistical significance of the effect of TB presence on the number of metastatic lymph nodes, and the lymphovascular and perineural invasion. A statistically meaningful correlation was found between the presence of TB and CRC survival (p = 0.016). Patients with right-sided colon cancer presented with worse overall survival (p = 0.011). The patients who presented lymph node metastases and TB presence had worse overall survival (p = 0.026 and p = 0.021, respectively). Tumour budding, tumour location, and age over 64 years are found to be the independent prognostic factors in CRC patients. Tumour budding is an important prognostic factor in CRC patients that will contribute to treatment. Pathological examination must consider TB in detail.
Keywords: colorectal cancer; prognosis; survival; tumour budding